Prevalence and risk factors associated with HIV/hepatitis B and HIV/hepatitis C co-infections among people who inject drugs in Mozambique - Cynthia Semá Baltazar; Makini Boothe; Timothy Kellogg; Paulino Ricardo; Isabel Sathane; Erika Fazito; Henry F. Raymond; Marleen Temmerman; Stanley Luchters (BMC, 2020)
Abstract Background There is scare information about HIV co-infections with hepatitis B virus (HBV) and/or hepatitis C virus (HCV) among People Who Inject Drugs (PWID) in Mozambique. This information is critical to ensure the treatment necessary to decrease the progression of liver disease and the transmission of both HIV and hepatitis. We assess the prevalence of HIV, HBV and HCV co-infections as well as associated risk factors among PWID. Methods The first Bio-Behavioral Surveillance Survey was conducted in 2013-2014 among persons who self-reported to have ever injected drugs. Using respondent-driven sampling, PWID aged 18 years and older were recruited in two cross-sectional samples in Maputo and Nampula/Nacala, two large urban centers of Mozambique. Rapid screening of HIV, HBV (HBsAg) and HCV was performed on site. Data from participants in both cities were pooled to conduct RDS-weighted bivariate analyses with HIV/HBV and HIV/HCV co-infections as separate outcomes. Unweighted bivariate and multivariate logistic regression analyses were conducted to assess correlates of co-infection. Results Among 492 eligible PWID, 93.3% were male and median age was 32 years [IQR: 27-36]. HIV, HBV and HCV prevalence were respectively 44.9% (95% CI:37.6-52.3), 32.8% (95% CI:26.3-39.5) and 38.3 (95% CI:30.6-45.9). Co-infections of HIV/HBV, HIV/HCV and HIV/HBV/HCV were identified in 13.1% (95% CI:7.2-18.9), 29.5% (95% CI:22.2-36.8) and 9.2% (95% CI:3.7-14.7) of PWID, respectively. Older age, history of needle/syringe sharing and history of injection with used needle/syringe was associated with HIV/HBV co-infection. Living in Maputo city, have older age, history of needle/syringe sharing and history of injection with used needle/syringe was associated with HIV/HCV co-infection. Conclusion There is a high burden of HBV and HCV among HIV-infected PWID in Mozambique. Our results highlight the need for targeted harm reduction interventions that include needle exchange programs and integrated services for the diagnosis and treatment of HIV, HBV and HCV to address these epidemics among PWID. Efforts should be made to strengthen ART coverage in the population as an important treatment strategy for both viruses.